Predictor of outcome after living donor liver transplantation for patients with hepatocellular carcinoma beyond the Japan criteria. Issue 4 (24th April 2020) - Yonemura, Yusuke; Yoshizumi, Tomoharu; Inokuchi, Shoichi; Kosai‐Fujimoto, Yukiko; Harada, Noboru; Itoh, Shinji; Toshima, Takeo; Takeishi, Kazuki; Yoshiya, Shohei; Mori, Masaki
Abstract: Background: The Japan criteria (JC, maximum tumor size within 5 cm, within five tumor nodules, AFP within 500 ng/mL or within Milan criteria) have been applied to cadaveric liver transplantation (LT) for hepatocellular carcinoma (HCC) and will be used for living donor LT (LDLT) in Japan. The aim of this study was to verify the JC in LDLT and to clarify the risk factor of HCC recurrence and mortality after LDLT beyond the JC. Patients and methods: Adult patients who underwent LDLT for end‐stage liver disease with HCC until October 2019 were reviewed retrospectively (n = 246). Patients were divided into two groups according to whether they were within JC (n = 203) or beyond JC (n = 43). Recurrence‐free or overall survival rates after LDLT were compared. Univariate and multivariate analyses were performed to identify risk factors of HCC recurrence and HCC‐related mortality after LDLT for patients beyond the JC. Results: Patients beyond the JC had significantly poorer 5‐year recurrence‐free (50.3% vs 95.9%, P < .001) or overall (61.7% vs 98.1%, P < .001) survival rates compared with patients within the JC. A multivariate analysis revealed that des‐gamma‐carboxy prothrombin (DCP) ≥ 300 mAU/mL (hazard ratio 9.36, 95% CI; 2.41‐36.4, P = .001) was an independent risk factor for HCC recurrence and HCC‐related mortality (hazard ratio 13.8, 95% CI; 1.92‐98.6, P = .01) after LDLT in patients beyond the JC. Conclusion: The outcome of LDLT for patients within the JC was favorable. Patients beyond the JC with DCP ≥ 300 mAU/mL might be contraindicated for LDLT. Abstract : The aim of this study was to clarify the risk factor of HCC recurrence and mortality after LDLT beyond the Japan criteria (JC). We revealed that des‐gamma‐carboxy prothrombin (DCP) ≥300 mAU/ml was an independent risk factor for tumor recurrence and recipient HCC‐related mortality after LDLT in patients beyond the JC.